On the role of the weight function in the truncation quality of High Dimensional Model Representation - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2008)
This paper investigates the role of the weight function in the quality of the High Dimensional Model Representation's (HDMR) truncations at different levels of multivariance. This is done by evaluating the additivity measurers at different levels of multivariance, for specified weight functions and targets for HDMR. The observations imply that the weight functions picking function values from regions where the addive nature of the target function dominates.
Keywords: weight function; multivariate approximation; High Dimensional Model Representation; additivity measurers